Improving the efficiency of separating machines equipped with flat oscillating sieves. Issue 1 (September 2021) - Tkachev, V; Borodin, N; Knyazev, A; Borovikov, R; Lebedev, V
Abstract: The article deals with the separating machines equipped with flat sieves with various types of holes used for cleaning from impurities and sorting into fractions by size. It is noted that the main disadvantage of these machines is that in the process of their operation, the openings of the sieves are clogged by the separation products, which leads to a decrease in the separation efficiency, as well as a decrease in the productivity of the machines. It is mentioned that the most acute problem of cleaning the openings of sieves is when separating tree seeds. It is possible to increase the efficiency of the separating machines by using cleaning mechanisms that allow the seeds stuck in the holes to be pushed out when the machines are operating. A mechanism for cleaning the holes of sieves is proposed, equipped with cylindrical working bodies on which gears are mounted that are engaged with toothed rails. In the course of experimental studies on the treatment of tree seeds, the dependences of the completeness of the separation of the separated fraction on the specific load of the sieve, as well as on the speed of rotation of the drive shaft of the cleaning mechanism, were obtained. It is established that with an increase in the rotation frequency of the crank shaft of the cleaning mechanism, the completeness of the separation increases. It is determined that the greatest increase in the completeness of separation from 76.0% to 85.8% is observed when used in the design of the cleaning mechanism of gears with a diameter of 30 mm. It is established that the use of a mechanism for cleaning the holes of sieves, equipped with cylindrical working bodies, allows to increase the efficiency of the process of separating tree seeds.